2013
DOI: 10.1186/2193-1801-2-87
|View full text |Cite
|
Sign up to set email alerts
|

Environmental judgment in early childhood and its relationship with the understanding of the concept of living beings

Abstract: The evidence collected concerning the biocentric judgment that young children express when evaluating human actions on the environment leads some scholars to suggest that an essential understanding of the notion of living beings should appear earlier than previously believed.This research project aims to study that assumption. To this end, young children’s choice when they are put in situation of having to compare and choose the most negative option between environmentally harmful actions and the breaking of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 58 publications
4
13
0
4
Order By: Relevance
“…This observation fits in well with a specific body of research concerning young children's graphical expressions on biological phenomena which accounts for a very weak variation, or even no differences at all, when it comes to comparing girls and boy's drawings on the issues of, for instance, plants [12,37], the sun [13], the structure of trees [17], the distinction of living and non-living things [32,38], ideas about micro-organisms [39], and animals [18], to name but a few.…”
Section: Discussionmentioning
confidence: 58%
“…This observation fits in well with a specific body of research concerning young children's graphical expressions on biological phenomena which accounts for a very weak variation, or even no differences at all, when it comes to comparing girls and boy's drawings on the issues of, for instance, plants [12,37], the sun [13], the structure of trees [17], the distinction of living and non-living things [32,38], ideas about micro-organisms [39], and animals [18], to name but a few.…”
Section: Discussionmentioning
confidence: 58%
“…Furthermore, this idea complements previous research that has shown that childhood is not free from environmental concerns [17,18] and that the interest in preserving the environment emerges before the first conceptual development in the field of biology [8].…”
Section: Introductionsupporting
confidence: 53%
“…In this regard, the normative assessment of how to treat plants does not correlate with an improvement in young children's ability to distinguish living things from inert entities [8]. This may indicate that the unique ethical state that young children seem to attribute to plant life may initially emerge in early childhood and, more importantly, independently of their conceptual evolution in the biological domain [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations